Meta‐organization design: Rethinking design in interorganizational and community contexts - Gulati, Ranjay; Puranam, Phanish; Tushman, Michael (Strategic Management Journal, 2012)
Abstract This article provides conceptual foundations for analyzing organizations comprising multiple legally autonomous entities, which we call meta‐organizations. We assess the antecedents of the emergence of such collectives and the design choices they entail. The article identifies key parameters on which such meta‐organizations' designs differ from each other. It also presents a taxonomy that elucidates how such forms of collective action vary and the constraints they must address to be successful. We conclude with implications for research on meta‐organizational design. Copyright © 2012 John Wiley & Sons, Ltd.